Examination of the Threats to the Auditor’s Independence in Ghana - Bedi, I.; Onumah, J.M. (My University, 2013)
In the wake of the recent corporate scandals/collapses in the US, Australia and elsewhere, attention has been drawn to the issues relating to auditors’ independence. This has affected to a large extent the degree of confidence that users of accounting information have in financial statement and has put the integrity of most auditors to question. This study therefore examines and ranks the threats to the auditor’s independence, tests for significant differences and assesses safeguards used in curbing these threats. Using snowball sampling technique, data were collected from thirty local audit firms in Ghana. The data was analysed to compute descriptive statistics such as mean and standard deviation. Inferential statistics was computed using the chi-square test. The study finds threats to auditor independence to be moderate among local firms. Also, there are no significant differences among firms based on length of existence. Continuing Professional Development programmes and personal values of accountants were found be the major source of safeguards in reducing the threats to acceptable level. The hospitality and neighbourliness imbedded in the African culture were found to be a contributory factor to the threat of familiarity. There is a need for a firm-wide policy by firms on close relationship, enforcement of ICA (Ghana) Code of Conduct and quality control reviews to check familiarity threats in Ghana.